2020
DOI: 10.1002/nop2.581
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' views and satisfaction of their clinical learning environment in Singapore

Abstract: Clinical education provides essential and irreplaceable learning opportunities for nursing students in their pre-registration nursing education. A plethora of studies had contended the importance of clinical education that contributes to their valuable learning experiences from two perspectives. Firstly, clinical education facilitates the integration and translation of nursing students' theoretical knowledge from academia to practice, thereby enabling apprenticeship-based learning in a realistic clinical setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
20
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 52 publications
9
20
2
4
Order By: Relevance
“…Equally, a Preceptorship program can be an effective tool in improving nursing students' self-efficacy as being influenced by preceptors 'teaching experience, personal qualities, interaction with students, and professional development' (Rambod, Sharif, & Khademian, 2018). Partnership and collaboration between faculty of nursing colleges and staff of affiliating institutions matter a lot, as Woo and Li (2020) concluded that "Involvement" would complement "Personalization" and "Task orientation" and finally holistic clinical learning experience can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Equally, a Preceptorship program can be an effective tool in improving nursing students' self-efficacy as being influenced by preceptors 'teaching experience, personal qualities, interaction with students, and professional development' (Rambod, Sharif, & Khademian, 2018). Partnership and collaboration between faculty of nursing colleges and staff of affiliating institutions matter a lot, as Woo and Li (2020) concluded that "Involvement" would complement "Personalization" and "Task orientation" and finally holistic clinical learning experience can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Menurut Sepang dan Tore (2017) kepuasan mahasiswa dalam pengalaman belajar praktik klinik keperawatan akan tercapai jika pembimbing klinik memberikan informasi, stimulasi serta dapat menciptakan situasi belajar yang menarik. Penelitian Woo et al (2020) didapatkan hasil kebanyakan mahasiswa keperawatan melaporkan kepuasan sedang terhadap lingkungan belajar klinis. Penelitian Onuoha et al, (2016) bahwa pembelajaran klinis dianggap lingkungan yang memuaskan, tetapi juga ada bukti ketidakpuasan dengan pengawasan klinis mahasiswa perawat dan hubungan dengan supervisor.…”
Section: Pendahuluanunclassified
“…Na podlagi tega smo oblikovali prvo raziskovalno vprašanje, Tabela 3: Zadovoljstvo s kliničnim usposabljanjem med študenti zdravstvene nege glede na njihove demografske in druge podatke V raziskavi smo ugotavljali tudi podporo, ki jo študenti čutijo s strani kliničnega mentorja. Raziskovalci se strinjajo, da je nudenje podpore ena izmed osnovnih nalog kliničnega mentorja in da močno vpliva na izkušnjo s kliničnim usposabljanjem (Papastavrou et al, 2016;Pramila-Savukoski et al, 2019;Woo & Li, 2020). Njegova vloga je predvsem vodenje in usmerjanje študentov z namenom pridobivanja kompetenc zdravstvene nege (Ramšak Pajk, 2016).…”
Section: Diskusijaunclassified
“…V naši raziskavi smo ugotovili tudi, da so klinični mentorji pri pripravi študenta na intervencijo zdravstvene nege zmerno inovativni in zanimivi. Do podobne ugotovitve sta prišla tudi Woo & Li (2020) pri anketiranju študentov zdravstvene nege v Singapurju, ki so pri svojih kliničnih mentorjih opazili pomanjkanje inovativnosti v pedagoškem procesu.…”
Section: Diskusijaunclassified